Serum free light chains and multiple myeloma: Is it time to extend their application?. Issue 4 (6th March 2020) - Markovic, Uros; Leotta, Valerio; Tibullo, Daniele; Giubbolini, Rachele; Romano, Alessandra; Del Fabro, Vittorio; Parrinello, Nunziatina Laura; Cannizzaro, Maria Teresa; Di Raimondo, Francesco; Conticello, Concetta
Abstract: In nonsecretory, oligo‐secretory, and light chain multiple myeloma patients, serial sFLC evaluation could precede biochemical and clinical disease progression, even in extramedullary relapse, thus initiating early treatment with novel anti‐MM agents. Abstract : In nonsecretory, oligo‐secretory, and light chain multiple myeloma patients, serial sFLC evaluation could precede biochemical and clinical disease progression, even in extramedullary relapse, thus initiating early treatment with novel anti‐MM agents.